Structure, function, and pharmacology of NMDA receptor channels - Vyklicky, V; Korinek, M; Smejkalova, T; Balik, A; Krausova, B; Kaniakova, M; Lichnerova, K; Cerny, J; Krusek, J; Dittert, I; Horak, M; Vyklicky, L (Physiological research, 2014)
NMDA receptors have received much attention over the last few decades, due to their role in many types of neural plasticity on the one hand, and their involvement in excitotoxicity on the other hand. There is great interest in developing clinically relevant NMDA receptor antagonists that would block excitotoxic NMDA receptor activation, without interfering with NMDA receptor function needed for normal synaptic transmission and plasticity. This review summarizes current understanding of the structure of NMDA receptors and the mechanisms of NMDA receptor activation and modulation, with special attention given to data describing the properties of various types of NMDA receptor inhibition. Our recent analyses point to certain neurosteroids as NMDA receptor inhibitors with desirable properties. Specifically, these compounds show use-dependent but voltage-independent block, that is predicted to preferentially target excessive tonic NMDA receptor activation. Importantly, neurosteroids are also characterized by use-independent unblock, compatible with minimal disruption of normal synaptic transmission. Thus, neurosteroids are a promising class of NMDA receptor modulators that may lead to the development of neuroprotective drugs with optimal therapeutic profiles.
Keywords: Ion Channel Gating; mozek; Humans; gating iontového kanálu; Brain Diseases; Structure-Activity Relationship; vztahy mezi strukturou a aktivitou; neuroprotektivní látky; Protein Conformation; Receptors, N-Methyl-D-Aspartate; lidé; zvířata; neurony; Neuroprotective Agents; Synaptic Transmission; receptory N-methyl-D-aspartátu; nemoci mozku; nervový přenos; Brain; Neurons; Animals; konformace proteinů